2005
DOI: 10.1071/fp05012
|View full text |Cite
|
Sign up to set email alerts
|

Structural modifications induced by Eutypa lata in the xylem of trunk and canes of Vitis vinifera

Abstract: Eutypa dieback, a devastating disease in grapevines, is caused by the fungal pathogen Eutypa lata, a wood-inhabiting fungus. E. lata acts by degrading wood tissues in the colonisation areas, and produces foliar symptoms. These striking symptoms have been attributed to the production of toxic metabolites by the pathogen, the most widely studied being eutypine. The aims of the study were to compare the effects of E. lata on xylem structure at the site of infection and in remote tissues. In healthy Vitis vinifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 26 publications
1
23
1
Order By: Relevance
“…Furthermore, these authors have shown that P. viticola induces an increase in stomatal aperture in the dark as opposed to the expected stomatal closure. Changes in the semi-permeable properties of plasma membranes are among the first host reactions to fungal infection (Lucas and Dickinson 1998), causing the accumulation of metabolites induced by abnormal phloem transport (Guimaraes and Stotz 2004;Rudelle et al 2005). In the pathogenesis of Pseudoperonosporales cubens such shifts towards strong sinks for nutrients have been reported, causing a massive transfer into the developing sporangia (Cohen et al 1971).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these authors have shown that P. viticola induces an increase in stomatal aperture in the dark as opposed to the expected stomatal closure. Changes in the semi-permeable properties of plasma membranes are among the first host reactions to fungal infection (Lucas and Dickinson 1998), causing the accumulation of metabolites induced by abnormal phloem transport (Guimaraes and Stotz 2004;Rudelle et al 2005). In the pathogenesis of Pseudoperonosporales cubens such shifts towards strong sinks for nutrients have been reported, causing a massive transfer into the developing sporangia (Cohen et al 1971).…”
Section: Discussionmentioning
confidence: 99%
“…1c). The type of wood decay that is caused by E. lata is classified as a soft rot (Rudelle et al. , 2005; Rolshausen et al.…”
Section: Eutypa Diebackmentioning
confidence: 99%
“…The degradation of the wood has been characterized by the death of vessel‐associated cells (Rudelle et al. , 2005).…”
Section: Eutypa Diebackmentioning
confidence: 99%
“…Thus, it is thought that the experimental design used in the present series of experiments may have contributed to non detection of significant differences between the treatments. Previous research on the effects of plant stress on response to pathogen challenge or disease symptom development suggested that stress (Ferreira et al 1999;Treutter 2005;Desprez-Loustau et al 2006), particularly carbohydrate stress (Rudelle et al 2005), may be important for decreasing vine defence response but also can reduce the ability of the pathogen to invade and establish depending on the timing of the stress. Desprez-Loustau et al (2006) reported that many of the positive drought-disease interactions involved increased severity or impact of the disease rather than increased incidence of infection and so the timing of stress is important.…”
Section: Discussionmentioning
confidence: 99%
“…However, many of the vines sampled were not expressing any symptoms of trunk diseases even when the pathogens were present. The pathogens of interest have been identified as wound invaders (Mundy & Manning 2010) and stress on the vines at the time of wounding has been reported as one possible factor that could influence vine response to pathogen invasion (Rudelle et al 2005;Desprez-Loustau et al 2006;Petit et al 2006;Mundy & Manning 2011). Carbohydrates are important both to the vine's defence mechanisms against wounding and to the wound invading process of many pathogens (Mundy & Manning 2011).…”
Section: Introductionmentioning
confidence: 99%